A Case with Hepatic Involvement Mimicking Metastatic Disease in Multiple Myeloma - Mert Erciyestepe; Tarık Onur Tiryaki; İpek Yönal Hindilerden; Gülçin Yeğen; Meliha Nalçacı (Case Reports in Hematology)
Multiple myeloma is a type of plasma cell disorder and can be seen in different forms. According to current knowledge, it is not a curable disease. Smoldering multiple myeloma (SMM) is an asymptomatic clonal plasma cell disorder and distinguished from monoclonal gammopathy of undetermined significance by a much higher risk of progression to multiple myeloma. We present a 53-year-old female patient who started with SMM which turned into multiple myeloma after four years. Despite 26 cycles of lenalidomide treatment, we performed the second autologous stem transplantation. After 12 years from the diagnosis of the disease, it was transformed into plasma cell leukemia and widespread nodular lesions were seen in the liver. Different presentations could be seen due to malignant plasma cell infiltrations or primary amyloidosis. Liver involvement is one of them and is less common than other organ involvement. We report a case of myeloma presenting with extensive nodular involvement in the liver and misdiagnosed as metastatic disease. It is important because of its rarity and change of the treatment approach.